Distinct Effector Programs of Brain-Homing CD8+ T Cells in Multiple Sclerosis - Steven C. Koetzier; Jamie van Langelaar; Marie-José Melief; Annet F. Wierenga-Wolf; Cato E. A. Corsten; Katelijn M. Blok; Cindy Hoeks; Bieke Broux; Beatrijs Wokke; Marvin M. van Luijn; Joost Smolders (Cells, 2022)
The effector programs of CD8+ memory T cells are influenced by the transcription factors RUNX3, EOMES and T-bet. How these factors define brain-homing CD8+ memory T cells in multiple sclerosis (MS) remains unknown. To address this, we analyzed blood, CSF and brain tissues from MS patients for the impact of differential RUNX3, EOMES and T-bet expression on CD8+ T cell effector phenotypes. The frequencies of RUNX3- and EOMES-, but not T-bet-expressing CD8+ memory T cells were reduced in the blood of treatment-naïve MS patients as compared to healthy controls. Such reductions were not seen in MS patients treated with natalizumab (anti-VLA-4 Ab). We found an additional loss of T-bet in RUNX3-expressing cells, which was associated with the presence of MS risk SNP rs6672420 (RUNX3). RUNX3+EOMES+T-bet− CD8+ memory T cells were enriched for the brain residency-associated markers CCR5, granzyme K, CD20 and CD69 and selectively dominated the MS CSF. In MS brain tissues, T-bet coexpression was recovered in CD20dim and CD69+ CD8+ T cells, and was accompanied by increased coproduction of granzyme K and B. These results indicate that coexpression of RUNX3 and EOMES, but not T-bet, defines CD8+ memory T cells with a pre-existing brain residency-associated phenotype such that they are prone to enter the CNS in MS.